Local Wisdom Of Gulai Umbut Undak Tapeghan Ikan In The Mangkal Luagh Tradition In Durian Sebatang Village, Kedurang District, South Bengkulu - Mentari, Gaya; Desmi W, Fenny; Syaputra, Een (SOCIAL PEDAGOGY: Journal of Social Science Education, 2025)
Gulai Umbut Undak Tapeghan Ikan is a traditional dish originating from Durian Sebatang Village, Kedurang District, South Bengkulu Regency. The availability of raw materials for making this curry is now declining due to the exploitation of the local environment. This has caused the local knowledge contained in Gulai Umbut Undak Tapeghan Ikan to erode and become vulnerable amid the tide of globalization. The purpose of this study is to examine the form of local knowledge values in Gulai Umbut Undak Tapeghan Ikan. The method used is qualitative descriptive with a cultural anthropology approach. Data collection was conducted through interviews and observations by observing the process of collecting ingredients such as umbut in the forest and fish in the river. Data analysis was carried out by sorting information based on the concept of local wisdom. The results of the study show that the local knowledge values contained in Gulai Umbut Undak Tapeghan Ikan are evident in the knowledge of the process of searching for raw ingredients for gulai, the skills involved in the process of cooking gulai, and the social integration created by the serving of gulai in the Mangkal Luagh tradition. The social integration of this food is evident when it is served in the Mangkal Luagh tradition. Gulai Umbut is a mandatory and special dish that must be made in every home as a requirement for the Mangkal Luagh tradition so that guests can try the local specialty.